2008
DOI: 10.1007/s11325-008-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the WristOx 3100™ oximeter for the diagnosis of sleep apnea/hypopnea syndrome

Abstract: A negative oximetry defined as ADI2 < or = 12.2 excluded SAHS defined as AHI > or = 5 or 10 with a sensitivity and negative likelihood ratio of 100% and 0%, respectively. Furthermore, a positive oximetry defined as an ADI3 > 32 (SAHS = AHI > or = 15) had a specificity of 100% to confirm the pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 51 publications
1
53
0
3
Order By: Relevance
“…Some previous studies 18,19,27,28 have validated this PM in the laboratory (i.e., concurrent with PSG) and reported good sensitivity (80% to 100%) to rule in OSA (AHI ≥ 5 events/h) but variable specificity (50% to 100%), with LR+ values ranging from 1.9 to infinity. Our study showed high diagnostic accuracy to rule in OSA with specificity 100% and LR+ infinity on the simultaneous night assessment.…”
Section: -11mentioning
confidence: 86%
See 2 more Smart Citations
“…Some previous studies 18,19,27,28 have validated this PM in the laboratory (i.e., concurrent with PSG) and reported good sensitivity (80% to 100%) to rule in OSA (AHI ≥ 5 events/h) but variable specificity (50% to 100%), with LR+ values ranging from 1.9 to infinity. Our study showed high diagnostic accuracy to rule in OSA with specificity 100% and LR+ infinity on the simultaneous night assessment.…”
Section: -11mentioning
confidence: 86%
“…Previous studies have one or more of the following limitations: (a) failure to study the PM device in its site of intended use, the home 18,19,27,28 ; (b) low sample size [16][17][18][19][20][21]27,28 ; (c) failure to collect oximetry data [16][17][18][19][20]27,29 ; (d) no randomization of order of comparison 18,19,27,28 ; and (d) no manual review of the raw PM data. [16][17][18][19][20]27,29,30 Our validation addresses these limitations.…”
Section: -11mentioning
confidence: 99%
See 1 more Smart Citation
“…35 ABPM was performed in a regular active day for a period of 24 hours through the validated SPACELABS HEALTHCARE ® device, model 90217A, 36 in the same arm on which the office evaluation was performed. The oximetry was collected using a finger sensor and performed through the validated device WristOx ® , model 3150SK-04.…”
Section: Variablesmentioning
confidence: 99%
“…The oximetry was collected using a finger sensor and performed through the validated device WristOx ® , model 3150SK-04. 35 The office BP values were obtained in two moments, one before and the other after the implementation of the ABPM device. A minimum of three measurements on each day were taken and the first measurement of each one was excluded.…”
Section: Variablesmentioning
confidence: 99%